2021
DOI: 10.1155/2021/3617498
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Traditional Chinese Medication‐Based Bioactive Compounds on Cellular and Molecular Mechanisms of Oxidative Stress

Abstract: The oxidative stress reaction is the imbalance between oxidation and antioxidation in the body, resulting in excessive production of oxygen free radicals in the body that cannot be removed, leading to excessive oxidation of the body, and causing damage to cells and tissues. A large number of studies have shown that oxidative stress is involved in the pathological process of many diseases, so inhibiting oxidative stress, that is, antioxidation, is of great significance for the treatment of diseases. Studies hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 117 publications
0
16
0
1
Order By: Relevance
“…From the established G-C-T-V network, we identified several key components and targets through multiple centrality assessments. Luteolin, a widely distributed flavonoid found in many herbal extracts ( 12 ), is known to be a potent antioxidant and is demonstrated to have protective actions against Ang II-induced VR, which could be mediated through attenuation of oxidative stress ( 40 ). Meanwhile, luteolin improved monocrotaline-induced right VR at least partly through suppressing HIPPO-YAP/PI3K/AKT signaling pathway ( 41 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From the established G-C-T-V network, we identified several key components and targets through multiple centrality assessments. Luteolin, a widely distributed flavonoid found in many herbal extracts ( 12 ), is known to be a potent antioxidant and is demonstrated to have protective actions against Ang II-induced VR, which could be mediated through attenuation of oxidative stress ( 40 ). Meanwhile, luteolin improved monocrotaline-induced right VR at least partly through suppressing HIPPO-YAP/PI3K/AKT signaling pathway ( 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, increased reactive oxygen species production or impaired antioxidant system could tilt the cell redox balance to oxidative imbalance and lead to the overproduction of reactive oxygen species ( 10 ). Oxidative stress is considered to be an important component of various diseases ( 11 ), including VR ( 12 ). In recent years, the study of the mechanism of oxidative stress in VR has achieved certain results ( 13 , 14 ), showing that oxidative stress may be one of the targets of anti-VR ( 15 , 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…Inflammatory signals seem to be more important in VR, which are associated with the intense activation of cytokine cascades (11)(12)(13). Furthermore, oxidative stress, apoptosis, and autophagy, transforming growth factor β1 (TGF-β1), neuroendocrine system, and peroxisome proliferatorsactivated receptor γ (PPARγ) are involved in VR regardless of etiology (13,14).…”
Section: Molecular Pathways Involved In Cardiac Remodelingmentioning
confidence: 99%
“…Oxidative stress is due to the loss of balance of redox between the level of ROS and endogenous antioxidant capacity, which causes the relative deficiency of antioxidant capacity and the relative increase of intracellular ROS (39)(40)(41). The increase of some toxic ROS leads to the loss of cell function, gene mutation, and even death (14,42). Studies have shown that ROS is related to myocardial infarction and myocardial hypertrophy (43,44).…”
Section: Oxidative Stressmentioning
confidence: 99%
“…Traditional Chinese medicine (TCM), mainly from the East, has shown its idiographic ascendancy in the prevention, therapeutic effect, rehabilitation, and healthcare of diverse diseases (14)(15)(16). The evidence-based application of TCM keeps a foothold in China and other Asian countries, and with the popularity of TCM in the East, it is increasingly accepted and used by other countries in the world (17,18).…”
Section: Introductionmentioning
confidence: 99%